A Mobile Learning Based-Creative Writing In Senior High School - Ernalida; Oktarina, Santi; Ansori (Universitas Pendidikan Ganesha, 2023)
In learning Indonesian, writing skills in high school are needed. However, in reality, secondary school students' creative writing abilities are still weak. Several studies state that high school students have yet to be able to write creatively optimally, and they are less motivated in the learning process. Based on the above, a solution is needed to overcome this. This study aims to describe the analysis of teacher needs for mobile learning-based learning media in creative writing learning in secondary schools to increase teacher and student literacy. The method used is the survey method. The sample of this research is 27 Indonesian language teachers. Data collection techniques used were questionnaires and interviews. The data analysis technique used is qualitative and quantitative analysis techniques. The results of the research show as follows. First, the media to be developed must comply with the principles of multimedia development, the characteristics of mobile learning, and the principles of learning to write. Second, there needs to be more learning media used so far. Third, teachers in secondary schools in Palembang need learning media based on mobile learning in learning creative writing.